Could the space probe Philae© be energized remotely?. Issue 2 (16th May 2019) - Costanzo, Alessandra; Roselli, Luca; Georgiadis, Apostolos; Carvalho, Nuno Borges; Takacs, Alexandru; Arpesi, Pier Giorgio; Martins, Rodolfo
Abstract : Space probes suffer from a fundamental problem, which is the limited energy available for their operation. Energy supply is essential for continuous operation and ultimately the most important sub-system for its sustainable functioning. Considering, for instance, the last space probe put on Comet 67P/Churyumov–Gerasimenko, called "Philae", which was sent by Rosetta (http://www.esa.int/Our_Activities/Space_Science/Rosetta ), to operate and to monitor comet activity, its operation was jeopardized due to the fact that it landed on a shadowed zone (no direct sunlight). Since its operational energy was only based on solar harvesters, the energy for its operation was limited by solar energy availability. In this paper a study on a viable alternative based on wireless power transmission is presented and discussed at the system level. It is proved that, using current technology, it is possible to create alternatives or supplement to existing power sources such as solar panels to power up these important space probes and to secure their operation.